Pengaruh Kompetensi Pedagogik Dan Motivasi Kerja Terhadap Keinovatifan Guru Dalam Pembelajaran Di Sekolah Menengah Pertama (SMP) - Fajria, Indah; Danim, Sudarwan (UNIVERSITAS BENGKULU, 2024)
The aim of this research is to describe the influence of pedagogical competence and work motivation on teachers innovativeness in learning (regression study in Public Junior High Schools in Pendopo and Muara Pinang Subdistricts, Empat Lawang Regency, South Sumatra). The method used was quantitative with a sample size of 82 teachers selected using simple random sampling techniques. Data processing techniques using product-moment correlation, determination, simple regression and multiple regression, t test, and F test. The results of the research; 1) There is a positive and significant between pedagogical competence on teacher innovativeness; 2) There is a positive and significant between work motivation on teacher innovativeness; 3) There is a positive and significant influence simultaneously between pedagogical competence and work motivation on teacher innovativeness.